Immunodeficiency and hemolytic uremic syndrome: a case report - Akçay, Nihal; Tosun, Demet; Bingöl, İlyas (The Turkish Journal of Pediatrics, 2025)
Background. Ataxia-telangiectasia (A-T) is a rare, autosomal recessive disorder characterized by cerebellar ataxia, oculocutaneous telangiectasia, and immunodeficiency, predisposing affected individuals to recurrent and severe infections. This case report presents a rare example of Shiga toxin-producing Escherichia coli (STEC)-associated hemolytic uremic syndrome (HUS) in a 12-year-old boy with a known diagnosis of A-T. To our knowledge, this is the first reported case of STEC-HUS in a patient with A-T.Case Presentation. The patient presented with vomiting and bloody diarhea Investigations revealed hemolytic anemia, thrombocytopenia, and acute kidney injury. The patient received intravenous immunoglobulin, albumin, and continuous renal replacement therapy and recovered.Conclusion. This case highlights the increased susceptibility of individuals with A-T to infections and the potential for life-threatening complications, such as HUS. The coexistence of A-T and STEC-HUS presentes unique challenges in diagnosis and management. Early recognition and targeted treatment led to a successful recovery and underscored the importance of close follow-up in immunodeficient patients.
Keywords: ataxia telangiectasia; hemolytic uremic syndrome; Shiga toxin; immunodeficiency